PSYCHOLOGICAL RESPONSE (STRESS) IN STROKE PATIENTS WITH PHYSIOTHERAPY PROGRAMS - Zuyina Lukluk Aningsih (Jurnal Riset Kesehatan, 2020)
Strokes can occur at any age, but the number of strokes increases with age. Stroke is caused by disruption of blood flow to the brain, usually because blood vessels rupture or are blocked by blood clots thereby cutting off the supply of oxygen and nutrients that cause damage to brain tissue. The purpose of this study is to describe the symptoms of stress in stroke patients. Data collection uses observation and interviews. Data validation techniques using triangulation of data sources and methods. The data analysis technique uses an interactive model of qualitative analysis. The results found that stroke sufferers generally experience stress, which is caused by the mind and mood, which is thinking about a disease that does not go away, and must be forced to depend on others when doing daily activities. Stress in stroke patients can be seen from physical, emotional, and behavioral signs. To reduce stress as well as an effort to relieve or cure a stroke, one with behavioral therapy is based on learning theory, and perform self-improvement psychologically or mentally, physically and socially, as well as spiritually.